Appalachia as a laboratory for contemporary rural-urban development - A. M. Nikulin (RUDN journal of Sociology)
The article is a review of C. Marshall Cook’s Big Rural: Rural Industrial Places, Democracy, and What Next (Lanham: Lexington Books, 2024). This is an original study of the long-term rural-urban transformations of the Appalachian region, especially the Pocahontas coal deposit: the author briefly reconstructs social history of this region which until the second half of the 20th century was one of the main drivers of economic - not only industrial but also rural - growth in the United States, but for the past half-century has been in a long-term depression caused primarily by the depletion of local natural resources, which led to unemployment and demographic depopulation. The book shows the causes of the long-term degradation of nature and society in Appalachia based on the STS approaches, in which the objects of research act as laboratories not only for scientific-technical but also for social-humanitarian experiments. Marshall Cook emphasizes the importance of preserving local knowledge as a condition for sustainable territorial development. At the same time, the book contains to a certain extent declarative-activist theses of active resistance to depression in the Appalachian region with awareness and recognition of the role and responsibility of science for the development of grassroots democracy.